The Development of Manpower and Economic Development : Is Co-ordination Possible? - Peitchinis, S. (Relations industrielles / Industrial Relations, 1967)
Canada has grossly neglected the development of her human resources. In addition, she has failed to establish the very basic requisites for the efficient functioning of the labour market. Considering that both labour and the labour market have been attributed significant roles in the process of economic growth, what must we do to ensure the attainment and maintenance of a balance between the qualitative and quantitative occupational composition of the labour force and the manpower requirements of the economy?